2020
DOI: 10.1002/cmdc.202000055
|View full text |Cite
|
Sign up to set email alerts
|

A Library of Thiazolidin‐4‐one Derivatives as Protein Tyrosine Phosphatase 1B (PTP1B) Inhibitors: An Attempt To Discover Novel Antidiabetic Agents

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is an important target for the treatment of diabetes. A series of thiazolidin‐4‐one derivatives 8–22 was designed, synthesized and investigated as PTP1B inhibitors. The new molecules inhibited PTP1B with IC50 values in the micromolar range. 5‐(Furan‐2‐ylmethylene)‐2‐(4‐nitrophenylimino)thiazolidin‐4‐one (17) exhibited potency with a competitive type of enzyme inhibition. structure–activity relationship studies revealed various structural facets important for the potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Patel et al [164] reported the synthesis of three series of thiazolidin-4-one derivatives and evaluation of their PTP1B inhibitory activity. Among all compounds, 111a-f (Figure 46) exhibited potent inhibitory activity with an IC50 values < 10 μM with compound 111e being the best competitive PTP1B inhibitor with an IC50 value of 5.88 ± Hidalgo-Figueroa et al [161] designed and synthesized two thiazolidine-2,4dione/benzazole derivatives (108a, 108b) as PTP1B inhibitors (Figure 43).…”
Section: Protein Tyrosine Phosphatase 1 B (Ptp1b) Inhibitorsmentioning
confidence: 99%
“…Patel et al [164] reported the synthesis of three series of thiazolidin-4-one derivatives and evaluation of their PTP1B inhibitory activity. Among all compounds, 111a-f (Figure 46) exhibited potent inhibitory activity with an IC50 values < 10 μM with compound 111e being the best competitive PTP1B inhibitor with an IC50 value of 5.88 ± Hidalgo-Figueroa et al [161] designed and synthesized two thiazolidine-2,4dione/benzazole derivatives (108a, 108b) as PTP1B inhibitors (Figure 43).…”
Section: Protein Tyrosine Phosphatase 1 B (Ptp1b) Inhibitorsmentioning
confidence: 99%
“…Most of the earlier drug discovery efforts were primarily focused on designing a generation of potent, selective, bioavailable PTP-based active-site inhibitors (pTyr mimetic). [20][21][22] However, several challenges emerged during targeting active-site of PTPs including the catalytic pTyr binding site is highly conserved among all PTPs superfamily, suggesting the difficulty to develop active-site targeted inhibitor for one isoform without inhibiting the activity of closely related isoforms, which in turn leads to off-target cellular effects. In addition, the active site is cationic in nature to facilitate the interaction with the negatively charged in pTyr site.…”
Section: Introductionmentioning
confidence: 99%
“…[83] Therefore, inhibitors of PTPs such as thiazolidine-4-ones are expected to have potential therapeutic value. [84] This fact has been validated by several researchers like 3. [89][90][91] This reduction of glucose to sorbitol is generally nonsignificant under the euglycemic condition that occurs at the cost of NADPH leading to decreased glutathione levels, resulting in oxidative stress.…”
Section: Ptp1bmentioning
confidence: 53%